Three-dimensional flow structures modelling based on a depth-integrated method in a sharply curved open channel over topography - Lugina Fikry Purwa; Uchida Tatsuhiko; Blanckaert Koen (E3S Web of Conferences)
In this study, we introduce the bottom velocity calculation (BVC) technique, a depth-integrated approach for modeling three-dimensional flow systems in the two-dimensional (2D) river management model framework. The method has been expanded to a general coordinate system and its applicability to flow in bends and meanders for the applications to rivers. The method was validated to a laboratory experiment conducted in a sharply curved channel over topography. The pattern of water surface elevation and vertical velocity distribution can be replicated by the BVC method’s models, which also show strong qualitative agreement with the experimental dataset and 3D model. The benefit of using the BVC technique instead of the 2D model is verified; the 2D model is unable to replicate the profile since it does not take into account three-dimensional flow structures. As seen above, the BVC method is helpful in evaluating the river environment because it can account for the complicated material transports caused by three-dimensional flows in the meandering sections of the river channel.